Anthropological perspectives on Myth (Anuário Antropológico, 2018)
In this paper, I explore anthropological interpretations of myths. Myths have fascinated scholars in various disciplines - as well as ordinary people. They have recorded and presented history, expounded philosophical ideas and moral values (Plato, Sophocles, Aeschylus), as well as provided patterns for interpreting language, (Müller), psychology (Freud, Rank, Jung) and structure (Lévi-Strauss, Greimas). One of the more puzzling moments in all these studies was the apparent incommensurability between “myth” and “reality.”